Assessment of ultraviolet and infrared radiation transmission through automobile windshields and side windows - Nouf Jubran AlQahtani; Ghada Naje AlEssa; Hoor Fayez AlDushaishi; Amnah Nabil Bukair; Syed Mehmood Ali (Frontiers in Public Health)
IntroductionExcessive exposure to solar radiation, particularly ultraviolet (UV) and infrared (IR) rays, poses significant health risks, including skin damage and an increased risk of skin cancer. While the penetration of UV radiation through vehicle windows is well-documented, the potential transmission of IR radiation remains less recognized.MethodsA total of 1,293 participants participated in a survey to assess awareness of solar radiation risks and protective behaviors, revealing a notable lack of attention to protective measures despite widespread knowledge of the risks associated with solar exposure. This study investigates UV and IR radiation exposure inside and outside vehicles in the Middle East, a region known for its extreme temperatures exceeding 52°C. Radiation levels were measured using a PMA2100 data logger radiometer in 20 vehicles.Results and discussionThe results demonstrated the ability of both UV and IR radiation to transmit through vehicle windows. For instance, the highest UV transmission through the side and front windows were recorded at 1.70 and 0.80 mW/cm2, respectively, while the IR transmission through the side and front windows were 84.17 and 98.27 mW/cm2, respectively. These findings highlight the need for improved protective measures against both UV and IR radiation, especially in hot climates where prolonged exposure to solar radiation is common. The study also identifies a gap in public awareness of IR radiation and calls for further research into effective strategies for mitigating these risks.